2017
DOI: 10.21037/jtd.2017.02.79
|View full text |Cite
|
Sign up to set email alerts
|

Chondromatous hamartoma of cervical esophagus: a case report and literature review

Abstract: Esophageal chondromatous hamartomas are very rare tumors, characterized by proliferating hyaline cartilage cells. We described the case of a 64-year-old woman, with a progressive foreign body sensation in the laryngopharynx caused by an intraluminal pedicled mass. Transcervical esophagectomy was performed and intraoperative biopsy revealed the mass was a cervical esophageal chondromatous hamartoma.The patient's postoperative course was uneventful and she recovered well. A review of the literature was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 29 publications
(26 reference statements)
0
8
1
Order By: Relevance
“…In our case EUS was not usable because of very proximal location of the tumour in the oesophagus but CT scan revealed cystic nature of the tumour and the tumour appeared benign in nature. In contrast to our finding Zhang et al have reported usefulness of EUS in the differential diagnosis of cervical oesophageal hamartomas (8).…”
Section: A B C a Bcontrasting
confidence: 99%
See 2 more Smart Citations
“…In our case EUS was not usable because of very proximal location of the tumour in the oesophagus but CT scan revealed cystic nature of the tumour and the tumour appeared benign in nature. In contrast to our finding Zhang et al have reported usefulness of EUS in the differential diagnosis of cervical oesophageal hamartomas (8).…”
Section: A B C a Bcontrasting
confidence: 99%
“…Previous reports have described intraluminal polypomatous descriptions of oesophageal hamartoma or lower intramural oesophageal hamartoma (2,3,5,14) or lower intramural oesophageal hamartoma (4). Hamartoma in cervical oesophagus of adults is extremely rare and only five case reports on this entity have been published this far (2,3,5,8,15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chondromatous hamartoma is an uncommon intramural lesion of the esophagus composed by hyaline cartilage, spindle cells, and glandular structures [ 50 ]. It represents <7% of all benign polypoid lesions of the esophagus and are mainly located between muscle and mucosal layer and can be endoscopically resected [ 3 , 50 ]. Differential diagnosis should firstly include low-grade chondrosarcoma, choristoma, and teratoma [ 50 , 51 ].…”
Section: Mesenchymal Hamartomasmentioning
confidence: 99%
“…It represents <7% of all benign polypoid lesions of the esophagus and are mainly located between muscle and mucosal layer and can be endoscopically resected [ 3 , 50 ]. Differential diagnosis should firstly include low-grade chondrosarcoma, choristoma, and teratoma [ 50 , 51 ].…”
Section: Mesenchymal Hamartomasmentioning
confidence: 99%